Cardiovascular and renal benefits of dapagliflozin in patients with short and long‐standing type 2 diabetes: Analysis from the DECLARE‐TIMI 58 trial. Issue 7 (12th March 2020) - Bajaj, Harpreet S.; Raz, Itamar; Mosenzon, Ofri; Murphy, Sabina A.; Rozenberg, Aliza; Yanuv, Ilan; Bhatt, Deepak L.; Leiter, Lawrence A.; McGuire, Darren K.; Wilding, John P. H.; Gause‐Nilsson, Ingrid A. M.; Sabatine, Marc S.; et al.
Abstract: Aim: To investigate whether the cardiovascular and renal benefits observed with dapagliflozin in the DECLARE‐TIMI 58 trial are also observed in patients with short and long‐standing diabetes. Materials and Methods: This post hoc analysis studied the dual primary efficacy endpoints, a composite of cardiovascular death or hospitalization for heart failure (CVD/HHF) and major adverse cardiovascular events (MACE; CVD, myocardial infarction [MI], ischaemic stroke) by diabetes duration. Results: Of the 17 160 patients, 3836 had diabetes duration of ≤5 years, 4731 >5‐10 years, 3952 >10‐15 years, 2433 >15‐20 years and 2206 >20 years. Dapagliflozin reduced the risk of CVD/HHF by a similar amount across diabetes duration subgroups, ranging from HR 0.79 (0.58‐1.06) in patients with diabetes duration of ≤5 years to 0.75 (0.55‐1.03) in those patients with diabetes duration of >20 years (interaction trend P ‐value 0.76). Hazard ratios (HRs) for MACE ranged from 1.08 (0.87‐1.35) in patients with diabetes duration of ≤5 years to 0.67 (0.52‐0.86) in those patients with diabetes duration of >20 years (interaction trend P ‐value 0.004). This was driven by greater reductions in the risk of MI and ischaemic stroke with dapagliflozin in patients with long‐standing diabetes (interaction trend P ‐values 0.019 and 0.015, respectively). The duration‐based MACE heterogeneity was apparent in those with or without a history of prior MI and in those with multiple risk factors. The renal‐specific outcome was reduced with dapagliflozin with HRs ranging from 0.79 (0.47‐1.34) in patients with diabetes duration of ≤5 years to 0.42 (0.25‐0.72) in those patients with diabetes duration of >20 years (interaction trend P ‐value 0.084). Conclusions: Dapagliflozin reduced the risk of CVD/HHF consistently, regardless of diabetes duration, whereas the treatment effect for MACE differed by duration subgroups, with significant reductions with dapagliflozin in patients with long‐standing diabetes.